Perkembangan Tokoh dan Agama Islam di Pakistan - Armansyah, Awang Dhany; Aziz, Akbar Nur (Universitas Muhammadiyah Yogyakarta, 2023)
Pakistan was founded on August 14, 1947, as one of the efforts of Pakistani Muslims in establishing a state based on the ideology of Islamic teachings. The purpose of this paper is to examine Islam and the figures who have contributed to Pakistan. The research method used is library research or library research. Writing data is done by collecting previous articles via the internet. The author's first step is to collect data from Google Search, Scopus and Google Scholar in the form of journal articles and other information needed in writing this research. After that the authors select and filter the data needed in this paper. The data that has been filtered is processed according to the needs of the writing. The results and discussion of this paper will be concluded in the closing section. The results of this study are a brief discussion of the Pakistani state and its establishment as a country based on Islamic ideology in its government, the beginning of Islam being entered and accepted by the Pakistani people and several figures have an important role in the sustainability of the State of Pakistan as an Islamic state. These figures include Sayyid Ahmad Khan, Muhammad Iqbal, Muhammad Ali Jinnah and Fazlur Rahman.